THE RISK OF MOTHERS LOSING AN ONLY CHILD IN CHINA. Issue 4 (8th October 2013) - JIANG, QUANBAO; LI, YING; SÁNCHEZ-BARRICARTE, JESÚS J.
Summary: China's one-child policy has been quite successful in bringing down the country's fertility level but has produced a large number of one-child families. The risk of one-child families losing their only child has not received enough attention. In this paper, using an extension of Goldman & Lord (1983 )'s method to measure widowhood, period life-table data from China's 2000 population census are used to examine age-specific and cumulative probabilities of mothers losing their only child. It is found that a mother faces a 14.94% probability of losing a son, and 12.21% probability of losing a daughter. As the age of first-time mothers increases, the probability of losing a child declines. Urban and rural mothers have different indices regarding the loss of children. Based on these findings the prospects for China's one-child policy are discussed.